Management of intracranial hemorrhage in severe factor V deficiency and definitive treatment with liver transplantation. (18th December 2017) - DesPain, Angelica W.; Kshetrapal, Anisha; Kousa, Youssef A.; Guelcher, Christine; Yazigi, Nada A.; Gonzalez, Corina E.; Nguyen, Vinh; Kroemer, Alexander; Kaufman, Stuart S.; Guerrera, Michael F.
Abstract: FV is primarily produced in the liver, and congenital FV deficiency is a disorder with an incidence of one in 1 million. Standard care is to treat severe bleeding phenotypes with FFP as there is no recombinant or plasma‐derived FV concentrate. We present a case of a neonate with known severe FV deficiency diagnosed after prolonged bleeding after circumcision who represented at age 2 months with a large left intraparenchymal hemorrhage. His bleed was treated with FFP, platelet transfusion, recombinant VIIa, and emergent evacuation. He was maintained on plasma infusions but was unable to space his infusions beyond 48 hours. Liver transplantation was considered as a definitive treatment for this condition. While awaiting a suitable liver, his FV trough levels occasionally dropped below 5%, and he suffered from a second acute intracranial bleed. He received an orthotopic liver transplant at age 5 months, resulting in correction of his FV levels. He has not required any plasma infusions post‐transplantation and has had no further bleeding episodes. Liver transplantation should be considered as definitive treatment early in the course for patients with severe FV deficiency and first time life‐threatening bleed.